On Mandelshtam as a Subtext in Iosif Brodsky’s “Lullaby of Cape Cod” - Barash, Olga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article identifies the set of texts by Osip Mandelshtam which served as possible sources of allusions for Iosif Brodsky’s poem “Lullaby of Cape Cod” (also related works by Bethea, Akhapkin and Ranchin are taken into account). The interrelations of the texts by the two authors are considered at the levels of lexis and motives. An attempt is made to analyze Brodsky’s quoting technique, as well as to interpret the “Lullaby of Cape Cod” in the context of Mandelshtam’s poetic world.